PENGARUH TATA KELOLA PERUSAHAAN TERHADAP KINERJA PERUSAHAAN: PERAN BIAYA KEAGENAN SEBAGAI MEDIASI - Candy Candy; Shelvi Shelvi; Johny Budiman (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This research aims to evaluate how corporate governance influences firm performance, considering the role of agency costs as mediation. The research sample consists of 120 manufacturing companies listed on the Indonesia Stock Exchange. The research data used quantitative data from companies' financial statements and annual reports from 2018 to 2022. The analysis method used is panel regression, and data validation was conducted using E-Views 12 software. The research results indicate that board size, managerial ownership, and institutional ownership do not significantly influence agency costs. However, agency costs significantly positively influence firm performance, as measured by ROA. Additionally, board size has a significant negative influence on firm performance. Meanwhile, managerial ownership and institutional ownership do not show a significant influence on firm performance. The mediation test results show that the influence of corporate governance on firm performance can’t be mediated by agency costs.